THE SOCIAL DIMENSION OF CRITICISM IN THE POEMS OF AHMET YURT DEDE - Süme, Gülda Çetindağ; Ekici, Muhammet Faruk (Ankara Haci Bayram Veli University, 2024)
The art of poetry, in which emotions and thoughts are expressed by giving different meanings to words, has been practiced almost from the birth of humanity to the present day. It is possible to see all the features of the language and culture of the societies practicing this art in the poems of the societies in question. In the history of Turkish culture, there have been personalities with different sacred characteristics who practiced this art, and these personalities were called bards. The bards performed their poems by playing the kopuzu, the most primitive form of today’s instrument. Their poems spread within the oral tradition, and the social and cultural characteristics of the period they lived in were passed on to the following periods in this way. Among the minstrels known as performers of folk poetry, those who belong to the Alevi-Bektashi faith have mostly prioritized love and affection, the trinity of Hak-Muhammad-Ali and human love. These minstrels, who can be considered within Alevi-Bektashi literature, also criticised the rude puritan, bigot, ignorance and people who prefer to be deprived of the blessings of education, mostly in a humorous language in their satirical poems emphasising the faulty aspects of society and individuals. Folk minstrel Ahmet Yurt Grandfather, who lived in the Hozat district of Tunceli and was one of the religious leaders of the Alevi-Bektashi faith, also wrote satirical poems. In these poems, he criticised the deterioration of Islamic and moral values, lack of education, ignorance, insatiable people, hypocrites, injustice and other faulty aspects of society. In this study, after giving brief information about the life, grandfatherhood and literary direction of Ahmet Yurt Grandfather, who was a descendant of Sarı Saltık and wrote about five hundred poems, his poems on satire will be evaluated by subjecting them to a certain classification. © 2024 Ankara Haci Bayram Veli University. All rights reserved.
AHMET YURT DEDE’NIN ŞIIRLERINDE ELEŞTIRININ TOPLUMSAL BOYUTU
Keywords: Ahmet Yurt Dede; Alevi Bektaşi Poetry; Criticism; Folk Poetry; Poet; Satire